School Actions to Prevent Gender-Based Violence: A (Quasi-)Systematic Review of the Brazilian and the International Scientific Literature - Prezenszky, Bruno C.; Galli, Ernesto F.; Bachega, Denise; de Mello, Roseli R. (Frontiers in Education, 2018)
The study aimed to provide scientific evidence to base school actions for the prevention of gender-based violence (GBV), specifically in the Brazilian context. Brazil presents high GBV indexes, ranking fifth in the world in femicide. Regarding violence in school, girls are the main victims of sexual and gender-based violence. Preventive actions must be taken to avoid such victimization. Searches conducted in Brazilian scientific databases retrieved no review of research on GBV prevention, so we conducted a thorough review of the topic, encountering a small number of articles in Brazilian databases. National and international scientific production on the theme were compared to identify if the low production is characteristic only in Brazil or in the international context as well. Searches were conducted in Brazilian and international databases using GBV and school-related descriptors. National data search retrieved 431 entries, while 222 papers were obtained in the international literature. The inclusion criteria for the analyses was the mention, in the abstract, of any form of action within school addressing GBV prevention. This screening selected eleven studies in the Brazilian databases and 30 articles in the international literature. Transformative or exclusionary elements were identified in the texts, focusing on different school levels and also lawmaking. Because of restrictions imposed by the data set, a descriptive analysis was conducted. In the international literature, it was possible to identify that recent research has been analyzing actions developed in school aiming GBV prevention and some of their impacts. Brazilian literature has been focusing primarily on describing actions rather than evaluating their impacts or describing GBV prevalence. The targeted population includes teachers, sports coaches, male and female students of different educational levels, whole school community, family and surrounding communities. The actions described in the international dataset are most frequently conducted in extracurricular context and are primarily focusing on raising awareness about GBV and providing information. The Brazilian studies indicate few actions conducted within the school. The analysis indicated characteristics in school-actions that contribute to GBV prevention and overcoming, such as working with the whole school-community, empowering women and strengthening egalitarian masculinities, bystander training and implementing laws and policies.